2017
DOI: 10.1038/s41598-017-01631-5
|View full text |Cite
|
Sign up to set email alerts
|

Using Chironomus dilutus to identify toxicants and evaluate the ecotoxicity of sediments in the Haihe River Basin

Abstract: To effectively manage a watershed and successfully restore a river system, it is very important to assess the toxicity of sediments and identify the substances causing the toxicity. Seventy-six sediments collected in the Haihe River Basin (HRB) in China were screened for acute toxicity using Chironomus dilutus. We found that sediments from more than 32% of sampling sites, distributed mainly in the Ziya tributary and along the estuary, were acutely toxic to midges. A toxicity identification evaluation showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…This is consistent with the diverse compounds we extracted from the gloves, including a number of phthalate compounds, the fungicide dithiocarbamic acid, and zinc dibutyldithiocarbamate, Zn­(DDC) 2 (Supplemental Information Figure S-2 and Table S-2). Zn­(DDC) 2 has demonstrated toxicological effects in both terrestrial and aquatic systems, , including as a leachate from other materials (i.e., paint) . For example, Ritchie et al identified significant toxicological effects of Zn­(DDC) 2 on another lumbriculid oligochaete, the epigeic earthworm Eisenia andrei .…”
Section: Results and Discussionmentioning
confidence: 99%
“…This is consistent with the diverse compounds we extracted from the gloves, including a number of phthalate compounds, the fungicide dithiocarbamic acid, and zinc dibutyldithiocarbamate, Zn­(DDC) 2 (Supplemental Information Figure S-2 and Table S-2). Zn­(DDC) 2 has demonstrated toxicological effects in both terrestrial and aquatic systems, , including as a leachate from other materials (i.e., paint) . For example, Ritchie et al identified significant toxicological effects of Zn­(DDC) 2 on another lumbriculid oligochaete, the epigeic earthworm Eisenia andrei .…”
Section: Results and Discussionmentioning
confidence: 99%